2011
DOI: 10.1121/1.3629135
|View full text |Cite
|
Sign up to set email alerts
|

Native dialect matters: Perceptual assimilation of Dutch vowels by Czech listeners

Abstract: Naive listeners’ perceptual assimilations of non-native vowels to first-language (L1) categories can predict difficulties in the acquisition of second-language vowel systems. This study demonstrates that listeners having two slightly different dialects as their L1s can differ in the perception of foreign vowels. Specifically, the study shows that Bohemian Czech and Moravian Czech listeners assimilate Dutch high front vowels differently to L1 categories. Consequently, the listeners are predicted to follow diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
2
18
1
Order By: Relevance
“…This claim that L2 perceptual patterns differ according to the native dialect is supported in a number of studies. For example, Moravian and Bohemian Czech listeners showed differential perceptual assimilation patterns of Dutch which seemed to correspond to differences in the acoustic realizations of their vowels in their native dialect (Chládková and Podlipský 2011). Likewise, Escudero and Williams (2012) showed that differences in the acoustic realizations of Iberian and Peruvian Spanish vowels led to differences in their discrimination accuracy of some Dutch vowel contrasts.…”
Section: Introductionmentioning
confidence: 98%
“…This claim that L2 perceptual patterns differ according to the native dialect is supported in a number of studies. For example, Moravian and Bohemian Czech listeners showed differential perceptual assimilation patterns of Dutch which seemed to correspond to differences in the acoustic realizations of their vowels in their native dialect (Chládková and Podlipský 2011). Likewise, Escudero and Williams (2012) showed that differences in the acoustic realizations of Iberian and Peruvian Spanish vowels led to differences in their discrimination accuracy of some Dutch vowel contrasts.…”
Section: Introductionmentioning
confidence: 98%
“…Crucially, this reflected the voicing assimilation rules of the respective L1 languages, which differ in the pre-sonorant context. Importantly, Chládková and Podlipský (2011) showed that learning L2 speech sounds contrasts is not only language-specific, but also variety-specific. They examined the cross-language perception of Dutch vowels by speakers of the Bohemian and Moravian varieties of Czech.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it is not until recently that the L1 regional variety been taken into account as a factor potentially influencing perception (e.g. Chládková and Podlipský 2011;Escudero et al 2011;Escudero and Williams 2012;Marinescu 2012) and production (e.g. Lew 2002;O'Brien and Smith 2010;Marinescu 2012) of L2 sounds.…”
Section: The Production and Perception Of Non-native Vowelsmentioning
confidence: 99%
“…For Peninsular Spanish speakers, the opposite held: they produced the vowels with significant durational but no spectral differences. Chládková and Podlipský (2011) investigated the influence of dialectal differences in Bohemian and Moravian Czech on Dutch vowel perception. Their study focused on the high front vowel region, in which Czech has fewer vowel phonemes than Dutch.…”
Section: The Production and Perception Of Non-native Vowelsmentioning
confidence: 99%